2012
DOI: 10.1007/s00226-012-0477-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the mechanical behaviour of thin slices of maturating green poplar wood using cyclic tensile tests

Abstract: International audienceIn this study, longitudinal cyclic tensile tests were performed on green wood samples of Populus cv I4551. Complex mechanical behaviour, such as permanent set in terms of displacement and strain-dependent stiffness, was found. A linear relationship between stiffness and strain enabled each sample to be characterized. A large-scale experimental campaign led to the observation of the evolution of temporal and spatial intra-ring mechanical behaviour of intra-ring sliced specimens during wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In this study, it is assumed that all cells have the same viscoelastic properties once they are matured. This approximation is consistent with the results of Pot et al (2013a). In addition, negligible differences were found by Pot et al (2013b) between the viscoelastic behaviour of OW and that of TW.…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…In this study, it is assumed that all cells have the same viscoelastic properties once they are matured. This approximation is consistent with the results of Pot et al (2013a). In addition, negligible differences were found by Pot et al (2013b) between the viscoelastic behaviour of OW and that of TW.…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…This stress profile can explain the difference in sign for the autonomous curvature of the slats. In a previous study [23], it was showed that infradensity increases until a distance of about 1.5 mm from the cambium; thus the cells are not fully matured until at least this distance, which corresponds to the thickness of the samples used in this study. This is consistent with the explanation proposed here to interpret the different directions of autonomous curvature.…”
Section: Resultsmentioning
confidence: 87%
“…E 0 mainly increases with wood-cell age for OW samples, but no clear evolution for TW samples appears. However, the measurement of the elastic modulus was not the objective of this study, and it can be measured by other means [22,23]. Except for E 0 , the variations in viscoelastic parameters with respect to wood-cell age appear very similar between OW and TW samples.…”
Section: Creep Tests Resultsmentioning
confidence: 96%
“…As reported by Thibaut et al (2001), the tendency of the material to deform in response to physico-chemical changes can result in stress of high magnitude only if the cell wall is already sufficiently stiff. To the best of our knowledge, information on the stiffening kinetics of wood cell wall layers is currently lacking and the only measurements available are at the tissue scale (Grozdits and Ifju, 1969;Pot et al, 2013a;2013b).…”
Section: Introductionmentioning
confidence: 99%